A Tokenization System to Secure Critical Data - Pujari, Chetana; Muniyal, Balachandra; Kulkarni, Aishwarya (International Journal of Engineering and Technology, 2018)
One of the recent developments in India is a major shift from cash to cashless transaction which is going to bring in drastic change in the world of e-commerce. As transaction is a crucial task, the need for security is the prominent factor to consider. The proposed work aims to revise AES and develop a secure system based on tokenization.This method ensures no relation between actual credit card data and the token generated for it, so all the applications will be dealing with token but not the actual data. In tokenization there is no need to store token and corresponding data in a database instead a standard random value table is used to generate token, which reduces the overhead of storing tokens and ensures reduction in security audit.Â Â